Extraction associated with L-PRF grafting and immediate installation - Case reports (Research, Society and Development, 2022)
Within the regenerative procedures, fibrin rich in platelets and leukocytes (L-PRF) is discussed. The process for obtaining an L-PRF is considered simple, it starts with a venipuncture through the patient, where the use of anticoagulants is dispensed with. Considered as a second-generation platelet biomaterial, it is a means of concentrated and slow release of growth factors, enhancing bone neoformation. The objective of this work is to discuss, through 6 clinical case reports, the use of fibrin rich in platelets and leukocytes used after dental extraction procedures associated with the immediate installation of osseointegrated implants and its contribution to the success of the treatment. Bone gaps were compared at the time of extraction with implant placement and after the period of osseointegration, revealing total bone neoformation and osseointegration in the 6 cases presented. The bone types found varied from type I to IV, in the previously performed grafting sites. Therefore, the extraction technique associated with the installation of osseointegrated implants with the L-PRF and PFR-Block grafting technique is suggested to be safe, enabling bone neoformation and osseointegration.